Pengaruh Penggunaan Teknologi Informasi Terhadap Kinerja Pegawai Kantor Kecamatan Bulukumpa Kabupaten Bulukumba - Nurgawati Nurgawati (Journal of Communication Sciences (JCoS), 2020)
The background of this research is that there are still ASN employees at the Bulukumpa District Office who do not understand how to use computerized technology and are still reluctant to increase the potential for computerized use. Even though today, the use of information technology is very supportive of the success of the work of ASN employees. While the use of computerization in agencies is interconnected, the more facilities provided to users, the easier it is for users to access the data needed to complete tasks within the agency. This research was conducted by distributing questionnaires to all employees of the Bulukumpa District Office, totaling 22 respondents who were used as research samples. Based on the test results, the hypothesis can be accepted, that the use of information technology has a significant effect on employee performance. Based on the results of the simple regression test, it shows a significant influence between information technology on employee performance at the Bulukumpa District Office of 76.6%. This means that the magnitude of the influence of computerized technology on employee performance in completing work using computerization is 76.6%.